Analisis Kebutuhan dan Spesifikasi Lembar Kerja Peserta Didik dalam Pembelajaran Fisika - Syahbrudin, Johan (Universitas Halu Oleo, 2021)
This study aims to determine the importance of developing student worksheets in physics learning and the appropriate specifications to be developed. The method used is a systematic review with a meta-ethnographic approach to determine the required new student worksheets specifications. The research data were obtained from relevant scientific articles available in open access journals, then reviewed and analyzed using qualitative descriptive techniques. The results showed that it is necessary to develop a student worksheet that can improve students' soft skills and hard skills, namely student worksheets based on practicum with an emphasis on science process skills that are integrated with character values and assessment of science process skills by fulfilling the feasibility of aspects of content, language, presentation, and graphics. These findings are useful for educators as a reference in developing student worksheets in order to increase the effectiveness of physics learning both at the secondary school level and at the university level.